Comparison of Suture Anchor Repair and Suture Tape Augmentation for Reconstruction of the Anterior Talofibular Ligament: A Biomechanical Study - Qingfeng Shao; Dahai Hu; Xinru Chen; Huajun Wang; Lei Xiao; Qiang Teng; Jinsong Hong; Huige Hou; Xiaofei Zheng (Orthopaedic Surgery)
ABSTRACT Objectives Currently, there are various surgical options for the treatment of lateral ankle sprains, and deciding which surgical option to use is a question worth considering. Furthermore, there is a relative scarcity of mechanical research comparing suture anchor repair (SAR) and suture tape augmentation (STA) internal brace for the repair of the anterior talofibular ligament (ATFL). Therefore, this study aimed to compare the efficacy of arthroscopically all‐inside ATFL SAR and STA for reconstruction to treat lateral ankle sprains through biomechanical testing. Methods Eighteen fresh‐frozen cadaver ankles were used for the study and divided into one of three groups: (1) intact ATFL group, (2) arthroscopically reconstructed with suture tape augmentation internal brace of the ATFL (STA group), and (3) arthroscopically repaired ATFL with suture anchors (SAR group). We used custom fixtures to test the specimens for loading to ultimate failure and stiffness. Results The mean load to failure of the STA group (311.20 ± 52.56 N) was significantly higher than that of the intact ATFL group (157.37 ± 63.87 N; p = 0.0016) and the SAR group (165.27 ± 66.81 N; p = 0.0025). The mean stiffness of the STA group (30.10 ± 5.10 N/mm) was significantly higher than that of the intact ATFL (14.17 ± 6.35 N/mm; p = 0.0012) and the SAR group (15.15 ± 6.89 N/mm; p = 0.0021). The suture anchor repair withstood failure loads and stiffness similar to the intact ATFL. Conclusions In terms of failure load and stiffness, the reconstructive outcome of ATFL reconstruction with STA is markedly superior to that of SAR reconstruction of the ATFL and the intact ATFL. Additionally, the novel technique of the SAR was a reliable technique that offered biomechanical properties similar to intact ATFL.